Cervical aortic arch: an unusual cause of a pulsatile neck mass. (5th September 2018) - Steele, Lloyd; Silver, Benjamin; Beegun, Issa; Saleh, Hesham
Abstract : A 72-year-old man presented with epistaxis on two occasions requiring admission. Prior to performing a bilateral sphenopalatine artery ligation diathermy, anaesthetic concern was raised regarding what the patient described as a 'congenital aortic aneurysm', with an overlying scar secondary to explorative surgery as a child. The abnormality was a cervical aortic arch (CAA). CAA is a rare vascular anomaly, which most commonly manifests as a pulsatile neck mass. In this case, we discuss the differential diagnosis for a pulsatile neck mass and considerations to be made in the workup. We also highlight the importance of cardiovascular risk factor management in patients with CAA.